2023
DOI: 10.3390/molecules28031481
|View full text |Cite
|
Sign up to set email alerts
|

Novel Indole-Containing Hybrids Derived from Millepachine: Synthesis, Biological Evaluation and Antitumor Mechanism Study

Abstract: Millepachine, a bioactive natural product isolated from the seeds of Millettia pachycarpa, is reported to display potential antitumor activity. In this study, novel indole-containing hybrids derived from millepachine were designed, synthesized and evaluated for their antitumor activities. Among all the compounds, compound 14b exhibited the most potent cytotoxic activity against five kinds of human cancer cell lines, with IC50 values ranging from 0.022 to 0.074 μM, making it almost 100 times more active than mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This investigation results underline the importance of chaetocin in lung cancer control. The basal ROS accumulation level is higher than normal counterparts and more vulnerable to A549 cells [17, 37]. This study reports a significant level of ROS increases and mitochondrial membrane damage‐induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 79%
“…This investigation results underline the importance of chaetocin in lung cancer control. The basal ROS accumulation level is higher than normal counterparts and more vulnerable to A549 cells [17, 37]. This study reports a significant level of ROS increases and mitochondrial membrane damage‐induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 79%
“…Compounds derived from indole have gained considerable attention for their biological and pharmaceutical activities. [6,7] Indole plays a pivotal role in diverse biochemical reactions within the body, influencing aspects of bacterial physiology such as spore formation, plasmid stability, drug resistance, biofilm formation, and virulence. [8] Indole scaffolds are prevalent in crucial synthetic drug molecules, offering a reliable pathway for creating effective targets and binding to multiple receptors with high affinity, thus facilitating the development of new biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This nitrogen‐based heterocycle holds notable significance in the development of heterocyclic scaffolds. Compounds derived from indole have gained considerable attention for their biological and pharmaceutical activities [6,7] . Indole plays a pivotal role in diverse biochemical reactions within the body, influencing aspects of bacterial physiology such as spore formation, plasmid stability, drug resistance, biofilm formation, and virulence [8] …”
Section: Introductionmentioning
confidence: 99%
“…SAR was determined, and mechanistic investigations revealed that compound A caused cell-cycle arrest, specifically at the G2/M phase, inhibited tubulin polymerization, and induced cell apoptosis by accumulating reactive oxygen species and collapsing mitochondrial membrane potential. Importantly, compound A exhibited low toxicity to normal cells and showed effectiveness against drug-resistant cells, suggesting its potential for developing antitumor drugs [ 10 ]. The research primarily focused on Hypsizygus marmoreus ( H. marmoreus ) and explored its indole compounds and other bioactive constituents.…”
mentioning
confidence: 99%
“…Researchers conducted a study to discover new bioactive compounds by combining molecules with biological properties to produce indole derivatives. Ten (10) derivatives were synthesized, featuring different moieties at the C-3 position. The compounds were characterized for their antibacterial, antioxidant, and fungicidal activities.…”
mentioning
confidence: 99%